1988
DOI: 10.1177/0148607188012003265
|View full text |Cite
|
Sign up to set email alerts
|

Fiber supplementation of enteral formulas: effects on the bioavailability of major nutrients and gastrointestinal tolerance

Abstract: Two fiber-supplemented enteral formulas were recently introduced for patient application, Susta II and Enrich (12.4-g and 38.5-g soy polysaccharide/2000 kcal, respectively). This investigation had a 3-fold purpose: to determine if and to what extent fiber-supplementation changes the chemical composition of stool relative to a fiber-free formula (Ensure); to establish the clinical tolerance of the two new formulas; and to quantify the effects of soy polysaccharide on nutrient bioavailability. The study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 2 publications
1
21
0
1
Order By: Relevance
“…In 18 of 38 (47%) studies, feeding was administered via a nasogastric tube; 28–31, 35, 36, 39, 40, 42, 49, 50, 53, 58, 60, 65, 66, 68, 71 …”
Section: Resultsmentioning
confidence: 99%
“…In 18 of 38 (47%) studies, feeding was administered via a nasogastric tube; 28–31, 35, 36, 39, 40, 42, 49, 50, 53, 58, 60, 65, 66, 68, 71 …”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of the fiber arm of the study, the albumin was 3.2 ± 0.3 g/dL (normal 3.5-5), cholesterol was 152 ± 9 mg/dL (normal <200), and hemoglobin was 12.6 ± 2.0 g/dL (normal [14][15][16][17][18]. At the conclusion of this arm of the study values of 3.3 ± 0.2, 155 ± 11, and 12.9 ± 1.8, respectively, were noted.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, other normal subjects studied in a crossover manner using 25 g of soy fiber had no change in transit time, but did have an increase in fecal output [14]. In patients receiving tube feedings which contained fiber at dosages of 15-40 g/day, no changes were noted in fecal output [15,16]. Thus, the effects of soy polysaccharide upon fecal weight and transit time appear to be clinically inconsistent.…”
Section: Discussionmentioning
confidence: 95%
“…The soy polysaccharides (Scheppach et al, 1990;Kapadia et al, 1995;Lien et al, 1996) are being used as sources of dietary fiber in most of the enteral foods. The breakdown fraction of the dietary fiber of the enteral foods serves as a major fuel to the intestinal villi in the form of short-chain fatty acids (mainly butyrates), besides contributing to the other well-known physiological benefits of the dietary fiber (Heymsfield et al, 1988;Frankenfield and Bayer, 1989;Rays et al, 2005). Several investigators have reported the beneficial effects of probiotics especially of lactic acid bacteria (LAB) in terms of colonization of intestinal microflora, reduction in lactose intolerance, minimization of bacterial translocation, and enhancement of immune status among others (Gilliland and Speck, 1977;Puhan and Zambrini, 1992;Schiffrin et al, 1995;Helander et al ., 1997;Patider and Prajapati, 1997;Klaenhammer et al, 2005;Rays et al, 2005;Xiao et al, 2006).…”
Section: Formulation Of Enteral Foods Introductionmentioning
confidence: 99%